Myocardial infarction after blunt chest trauma incurred during rugby football that later required cardiac transplantation. Issue 4 (April 1986) - Watt, A H; Stephens, M R
Abstract : A 28 year old man sustained an extensive anterolateral myocardial infarction five minutes after a blow on the chest while playing rugby football. The resulting persistent cardiac failure necessitated orthotopic cardiac transplantation.